Fragments of libertarianism and neoliberal ascendancy: Ideological features and limitations of the liberal breakthrough in Finland - Kärrylä Ilkka; Strang Johan; Wuokko Maiju (Taylor & Francis, 2025)
This article explores the fragmentary history of libertarianism in Finland. We identify actors who have advanced libertarian ideas and agendas between 1970 and 2000 and discuss the purposes for which they have been mobilized in a Finnish context. Theoretically, we emphasize the primacy of local political cultures and context in the transnational circulation of political ideologies. In Finland, the introduction of libertarianism was contingent particularly upon foreign policy developments. Empirically, we proceed from the observation that Finland was a Nordic latecomer. Programmatic libertarian views, or serious discussions of Ayn Rand or Murray Rothbard, were conspicuously absent in Cold War Finland, and even in the 1990s they figured primarily as a subculture on the nascent World Wide Web. However, when more broadly understood as a positive emancipatory promise of individual freedom, libertarian ideas were important in pushing for a liberal turn in Finnish politics and society in the 1980s and 1990s. In the end, however, anti-statist and cultural libertarianism were subsumed by statist and economic neoliberalism.